Pengaruh Kombinasi Enzim Papain Dan Enzim Bromelin Terhadap Pemanfaatan Pakan Dan Pertumbuhan Ikan Kerapu Macan (Epinephelus fuscogutattus) - Taqwdasbriliani, Ertris Bergas; Hutabarat, Johannes; Arini, Endang (Journal of Aquaculture Management and Technology, 2013)
Tiger grouper has an economically value but the growth it is slower than the other fish species. Additional enzymes in the feed to maximize protein utilization by cultivan. Papain and bromelain enzymes is an exogenous enzymes which support in hydrolysis protein process. This research aimed to determine the effects of combination papain enzyme and bromelain enzyme to the Efficiency Feed Utilization (EFU), Protein Efficiency Ratio (PER) and Specific Growth Rate (SGR). This study was carried January to March 2013 in Laboratory of Brackish Water Aquaculture Development Centre Jepara. The fish samples which were used is tiger grouper in average weight 10.49±1.26 g and length 8.13±0.17 cm in the total amount of 180 tail. The experimental method use was Completely Random Design (CRD) consists of 6 treatment : A (100% papain), B (75% papain dan 25% bromelain), C (50% papain and 50% bromelain), D (25% papain and 75% bromelain), E (100% bromelain) and F (without adding enzymes) each treatment was replicated 3 times. Data analyzed by One Way Anova follow by Duncan Test. Result of the study revealed that the combination of additional papain and bromelain enzyme in the experimental feed can increase EFU, PER and SGR for tiger grouper. B treatment appear to be the best EFU (45.862±0.444%), PER (97.579±0,946%), SGR (1.210±0.037%/day), SR (100%).